Globalisasi Dalam Paradigma Structure-Conduct-Performance : Studi Kasus Industri Fast-Moving Consumer Goods di Indonesia - Shella Mutia Putri; Ima Amaliah (Universitas Pasundan, 2025)
This study examines the structure–conduct–performance (SCP) framework and firm strategy in sustaining market dominance in the fast-moving consumer goods (FMCG) industry. A quantitative descriptive approach was employed using secondary data from 78 FMCG companies listed on the Indonesia Stock Exchange (IDX). The data were analyzed using SmartPLS with the CB-SEM method. The results indicate a statistically significant bidirectional causal relationship between market structure, firm behaviour, and firm performance, supporting the dynamic nature of the SCP framework. The Indonesian FMCG industry is characterized by a highly concentrated market structure, where dominant firms implement diversification and differentiation strategies to strengthen competitive advantage and reinforce market power, potentially leading to monopolistic tendencies within specific product segments. The discussion highlights that geographical diversification and domestic market expansion are effective strategic responses to global integration pressures, enabling firms to sustain performance while managing competitive intensity and regulatory risks. Keywords: Market Structure, Corporate Strategy, Economic Globalization